Plasma Steroid Metabolome Profiling for Diagnosis and Subtyping Patients with Cushing Syndrome. (1st March 2018) - Eisenhofer, Graeme; Masjkur, Jimmy; Peitzsch, Mirko; Di Dalmazi, Guido; Bidlingmaier, Martin; Grüber, Matthias; Fazel, Julia; Osswald, Andrea; Beuschlein, Felix; Reincke, Martin
Abstract: BACKGROUND: Diagnosis of Cushing syndrome requires a multistep process that includes verification of hypercortisolism followed by identification of the cause of adrenocortical hyperfunction. This study assessed whether pituitary, ectopic, and adrenal subtypes of Cushing syndrome were characterized by distinct plasma steroid profiles that might assist diagnosis. METHODS: In this retrospective cross-sectional study, mass spectrometric measurements of a panel of 15 plasma steroids were applied to 222 patient samples tested for Cushing syndrome. Disease was excluded in 138 and confirmed in 51 patients with pituitary Cushing syndrome, 12 with ectopic adrenocorticotropin secretion, and 21 with adrenal disease. Another 277 age- and sex-matched hypertensive and normotensive volunteers were included for comparison. RESULTS: Compared with patients without disease, the largest increases in plasma steroids among patients with Cushing syndrome were observed for 11-deoxycortisol (289%), 21-deoxycortisol (150%), 11-deoxycorticosterone (133%), corticosterone (124%), and cortisol (122%). Patients with ectopic disease showed the most prominent increases, but there was considerable variation for other steroids according to subtype. Patients with adrenal disease had the lowest concentrations of androgens, whereas those with ectopic and pituitary disease showed the lowest concentrations of aldosterone. Plasma 18-oxocortisol was particularly low in ectopic disease. With the use of 10 selected steroids, subjects with and without different Cushing syndrome subtypes could be discriminated nearly as closely as with the use of salivary and urinary free cortisol, dexamethasone-suppressed cortisol, and plasma adrenocorticotropin (9.5% vs 5.8% misclassification). CONCLUSIONS: Patients with different subtypes of Cushing syndrome show distinctive plasma steroid profiles that may offer a supplementary single-test alternative for screening purposes.